Prognostic signature of lipid metabolism associated LncRNAs predict prognosis and treatment of lung adenocarcinoma - Zhao, Jie; Li, Guangjian; Zhao, Guangqiang; Wang, Wei; Shen, Zhenghai; Yang, Yantao; Huang, Yunchao; Ye, Lianhua (Frontiers in Oncology, 2022)
Background: Lung adenocarcinoma (LUAD) is the most predominant histological subtype of lung cancer. Abnormal lipid metabolism is closely related to the development of LUAD. LncRNAs are involved in the regulation of various lipid metabolism-related genes in various cancer cells including LUAD. Here, we aimed to identify lipid metabolism-related lncRNAs associated with LUAD prognosis and to propose a new prognostic signature. Methods: First, differentially expressed lncRNAs (DE-lncRNAs) from the TCGA-LUAD and theGSE31210 dataset were identified. Then the correlation analysis between DE-lncRNAs and lipid metabolism genes was performed to screen lipid metabolism-related lncRNAs. Cox regression analyses were performed in the training set to establish a prognostic model and the model was validated in the testing set and the validation set. Moreover, The role of this model in the underlying molecular mechanisms,immunotherapy and chemotherapeutic drug sensitivity analysis was predicted by methods such as Gene Set Enrichment Analysis，immune infiltration, tumor mutational burden (TMB), neoantigen, TIDE, chemosensitivity analysis between the high- and low-risk groups. The diagnostic ability of prognostic lncRNAs has also been validated. Finally, we validated the expression levels of selected prognostic lncRNAs by quantitative real-time polymerase chain reaction (qRT-PCR). Results:The prognostic model was constructed based on four prognostic lncRNAs (LINC00857, EP300-AS1, TBX5-AS1, SNHG3) related to lipid metabolism. The receiver operating characteristic curve (ROC) and Kaplan Meier (KM) curves of the risk model showed its validity. The results of GSEA suggested that differentially expressed genes in high- and low-risk groups were mainly enriched in immune response and cell cycle. There were statistically differences in TMB and neoantigen between high- and low-risk groups. Drug sensitivity analysis suggested that patients with low risk scores may have better chemotherapy outcomes. The results of qRT-PCR were suggesting that compared with the normal group, the expressions of EP300-AS1 and TBX5-AS1 were down-regulated in the tumor group, while the expressions of LINC00857 and SNHG3 were up- regulated. The four prognostic lncRNAs had good diagnostic capabilities, and the overall diagnostic model of the four prognostic lncRNAs was more effective. Conclusion: A total of 4 prognostic lncRNAs related to lipid metabolism were obtained and an effective risk model was constructed.